Urban Form Types and Some Related Social Problems of Multistorey - Hameed, Faisal Hameed; Areare, Mohammed Areare (Iraqi Journal of Architecture and Planning, 2018)
The urban expansion of the Gulf cities included many multi-storey housing projects of urban form types similar to those built in Britain during the post Second Wold War period of reconstruction. According to the literature, these types of urban form are associated with a number of social problems in relation to the health of some residents, anti-social behaviour of some youngsters, and some types of crime. The aim of this research is to identify the types of urban form in the context of the British built environment and to conduct a pilot study to investigate the presence of social problems in Gulf housing projects which encompass urban forms similar to those built in Britain during the post Second Wold War period. The conclusion is that some social problems can be traced in some of the projects inspected in the study. The study suggest further in depth research to determine the extent of such social problems and suggest design some guidance for new projects in order to avoid such problems.